2010
DOI: 10.5194/nhess-10-831-2010
|View full text |Cite
|
Sign up to set email alerts
|

Microseismic activity analysis for the study of the rupture mechanisms in unstable rock masses

Abstract: Abstract. Rockfalls are common instabilities in alpine areas and can cause significant damage. Since high mountains have been affected by an increasing number of these phenomena in the last years, a possible correlation with permafrost degradation induced by climate change has been hypothesized.To investigate this topic, a monitoring system, made of 5 triaxial geophones and 1 thermometer, was installed in 2007 at the Carrel hut (3829 m a.s.l., Matterhorn, Northwestern Alps), in the frame of the Interreg IIIA A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 22 publications
2
53
0
1
Order By: Relevance
“…The most important concentration of MS activity (Fig. 12) occurs for rapid and intense lowering of air temperature during both cold and warm seasons as already reported in Amitrano et al (2010). Minor concentrations of MS events can also be observed during the summer months when air temperature locally rises above 0 • C. As already described in Sects.…”
Section: Comparison Between Ms Data and Air Temperature Recordssupporting
confidence: 54%
See 2 more Smart Citations
“…The most important concentration of MS activity (Fig. 12) occurs for rapid and intense lowering of air temperature during both cold and warm seasons as already reported in Amitrano et al (2010). Minor concentrations of MS events can also be observed during the summer months when air temperature locally rises above 0 • C. As already described in Sects.…”
Section: Comparison Between Ms Data and Air Temperature Recordssupporting
confidence: 54%
“…The characteristics of the MS monitoring system installed in 2007, the reasons of the site choice and the details of the geomorphological setting of the area are detailed in Amitrano et al (2010). Hereinafter, the improvements and the characteristics of the empowered and renovated system are presented.…”
Section: Description Of the Ms Monitoring Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…While large thermal stresses can only occur close to the rock surface, ice formation in pores, cracks and fractures can potentially generate large stresses at greater depths, as suggested by theoretical and lab studies. Reporting a preliminary analysis of the microseismic activity monitored at a high alpine ridge, Amitrano et al (2010) recently stressed the importance of ice formation in fractures as they observed micro-seismic activity corresponding with particular trends of the temperature that could enhance ice formation. But the lack of details in the spatial and temporal distribution of the seismic events precluded the full understanding of the relationship between temperature evolution and related ice formation at small spatial scale and the triggering of seismic events.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that have monitored AEs in outdoor conditions have been restricted to short time periods, during which the monitoring system was carefully protected from the changing environmental conditions in a nearby heated building, for example (Cheon et al, 2011;Amitrano et al, 2010Amitrano et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%